Increased paediatric hospitalizations for empyema in Australia after introduction of the 7-valent pneumococcal conjugate vaccine - Roxanne E Strachan; Thomas L Snelling; Adam Jaffé (The World Health Organization, 2013)
OBJECTIVE: To examine rates of paediatric hospitalization for empyema and pneumonia in Australia before and after the introduction of the seven-valent pneumococcal conjugate vaccine (PCV7). METHODS: Rates of paediatric hospitalization for empyema and pneumonia (bacterial, viral and all types) were calculated following the codes of the International Classification of Diseases, tenth revision (ICD-10) as a principal diagnosis. The expected number of hospitalizations after the PCV7 was introduced was estimated on the basis of the observed number of hospitalizations before the introduction of the PCV7. Incidence rate differences (IRDs) and incidence rate ratios (IRRs) were calculated. Hospitalization incidence in each study period was expressed as the number of hospitalizations per million (10(6)) person-years. The population of children aged 0-19 years in Australia from 1998 to 2004 and from 2005 to 2010, as reported by the Australian Bureau of Statistics, was used to calculate the number of person-years in each period. FINDINGS: In the 5 years following the introduction of the PCV7, hospitalizations for pneumonia were fewer than expected (15 304 fewer; 95% confidence interval, CI: 14 646-15 960; IRD: −552 per 10(6) person-years; 95% CI: −576 to −529 per 10(6) person-years; IRR: 0.78; 95% CI: 0.77-0.78). Hospitalizations for empyema, on the other hand, were more than expected (83 more; 95% CI: 37-128; IRD: 3 per 10(6) person-years; 95% CI: 1-5 per 10(6) person-years; IRR: 1.35; 95% CI: 1.14-1.59). Reductions in hospitalizations were observed for all ICD-10 pneumonia codes across all age groups. The increase in empyema hospitalizations was only significant among children aged 1 to 4 years. CONCLUSION: The introduction of the PCV7 in Australia was associated with a substantial decrease in hospitalizations for childhood pneumonia and a small increase in hospitalizations for empyema.